Communication Strategies in English Conversations - Puthut Ardianto (Universitas Muhammadiyah Yogyakarta, 2016)
This research aims to reveal communication strategies used by students of the English Education Department of a university in Indonesia in English conversations and to find out the moments when the strategies were used. This research employed an interlanguage analysis. There were four par- ticipants who were asked to converse under a certain picture and was audio-recorded, transcribed, coded, and analysed. The findings show that the participants employed thirteen strategies when they were having English conversations.